The Use of an Android-Based Arabic Dictionary in the Arabic-Indonesian Tarjamah Course at the University - Hasnah Atikah; Imam Fauji (Universitas Muhammadiyah Sidoarjo, 2022)
This article aims to find out the use of an Android-based Arabic dictionary in the Arabic-Indonesian tarjamah course at the Arabic Language Education Study Program, University of Muhammadiyah Sidoarjo in 2021/2022. The approach that the researcher uses is a qualitative approach using data collection techniques through observation, interviews, and documentation. The results showed that, 1) The use of an Android-based Arabic dictionary, namely initially students had to open the dictionary application they wanted to use, change the keyboard to Arabic font, and type in words in the available columns. If the word is in the form of fi'il, it needs to be returned to fi'il madi, and if it is in the form of masdar, it can be typed directly. After clicking enter, various word search results will appear, students can choose the meaning according to the context. 2) The advantages of using an Android-based Arabic dictionary are that it can be owned by everyone, easy to carry, easy to use, fast in vocabulary search, and its contents are more complete than dictionary books. The drawback is that there is a possibility that the translation results from the dictionary are not in accordance with the context and the completeness of the contents in each dictionary application is different. 3) The way to overcome the shortcomings of using an Android-based Arabic dictionary is that students need to re-correct the meaning of the translation, switch the search to another Arabic dictionary application, ask friends, or use a dictionary book.